The Behavioural Features of Generalized Anxiety Disorder During the Perinatal Period: Identification, Assessment, and Diagnostic Implications - Inness, Briar E. (My University, 2025)
Generalized anxiety disorder (GAD) is a leading mental health condition, associated with significant distress and impairment, especially during pregnancy and the postpartum (perinatal) period. However, GAD is a poorly defined mental health disorder, and research devoted to understanding its clinical features is lacking. While excessive and difficult to control worry is the defining feature of GAD, there is growing interest in understanding the role of behaviour. Extant literature alludes to the diagnostic, clinical, and theoretical importance of behaviours in GAD, however, systematic evaluation of the behavioural features of GAD and their bearing on GAD pathology is lacking, particularly during the perinatal period. This dissertation explores the behaviours that perinatal individuals with GAD engage in, in response to their worries, adapts and validates a self-report measure to assess GAD behaviours during the perinatal period, and evaluates the contribution of specific behaviours to our diagnostic understanding of GAD. This program of research suggests that perinatal individuals with GAD engage in a range of avoidance and safety behaviours to manage their distress. We also provide clinicians and researchers with a measure of GAD behaviours for use during the perinatal period to support continued evaluation of this phenomenon. Finally, our research highlights the importance of checking behaviours in perinatal individuals with GAD, with potential implications for theory and practice.
THE BEHAVIOURAL FEATURES OF GENERALIZED ANXIETY DISORDER DURING THE PERINATAL PERIOD
Keywords: Pregnancy; Perinatal; Postpartum; Generalized Anxiety Disorder; Behaviour; Assessment